Positive influences of the application of inoculated lignocellulosic waste compost on the agronomic potential of a sandy loam soil - Fersi, Mariem; Louati, Ibtihel; Hadrich, Bilel; Smaoui, Yosr; Jerbi, Bouthaina; Jedidi, Naceur; Hassen, Abdennaceur; Hachicha, Ridha (Clean technologies and environmental policy, 2025)
Green waste contains large amounts of lignin, which resists biodegradation and therefore limits its composting process. To overcome this limitation, we have shown in some previous studies that fungal inoculation ( Trametes trogii ) during the maturation phase resulted in higher lignin degradation in compost C2 compared to control C1. The degradability was increased from 23 to 35%. Therefore, the aim of this study was to evaluate the effects of this reinforcement on the modeling of total organic carbon loss, fungal flora and laccase activity during the composting phases and on the final quality of composts C1 and C2 and their water extracts J1 and J2. The results found showed that carbon loss in both piles was subject to a first-order model (0–60 d) and a first-order E model (60–180 d). We found an increased total activity of mesophilic fungi and laccase in C2 immediately after inoculation (6 log10 UFC). Application of C2 significantly reduced soil bulk density BD by 29.5%, increased available water AW by 58% and improved dry biomass of wheat roots by 33% compared to 17.33 and 16% when C1 was applied. Graphical abstract